Neonatal Deaths in Rural Southern Tanzania: Care-Seeking and Causes of Death. (24th January 2012) - Mrisho, Mwifadhi; Schellenberg, David; Manzi, Fatuma; Tanner, Marcel; Mshinda, Hassan; Shirima, Kizito; Msambichaka, Beverly; Abdulla, Salim; Schellenberg, Joanna Armstrong
Abstract : Introduction. We report cause of death and care-seeking prior to death in neonates based on interviews with relatives using a Verbal Autopsy questionnaire. Materials and Methods. We identified neonatal deaths between 2004 and 2007 through a large household survey in 2007 in five rural districts of southern Tanzania. Results. Of the 300 reported deaths that were sampled, the Verbal Autopsy (VA) interview suggested that 11 were 28 days or older at death and 65 were stillbirths. Data was missing for 5 of the reported deaths. Of the remaining 219 confirmed neonatal deaths, the most common causes were prematurity (33%), birth asphyxia (22%) and infections (10%). Amongst the deaths, 41% (90/219) were on the first day and a further 20% (43/219) on day 2 and 3. The quantitative results matched the qualitative findings. The majority of births were at home and attended by unskilled assistants. Conclusion. Caregivers of neonates born in health facility were more likely to seek care for problems than caregivers of neonates born at home. Efforts to increase awareness of the importance of early care-seeking for a premature or sick neonate are likely to be important for improving neonatal health.